3D Printed Slotted Waveguide Array Antenna for D-Band Applications - Lomakin, Konstantin; Sippel, Mark; Helmreich, Klaus; Gold, Gerald (2021 15th European Conference on Antennas and Propagation (EuCAP), 2021)
In this work, an additively manufactured helix antenna for a center frequency of f c = 77 GHz is presented. A novel feed concept is proposed including a transition from the helix coil to an E-band waveguide, which allows for tuning of antenna matching. Measurements suggest a -15dB-bandwidth of B 15 dB =8 GHz and -10dB-bandwidth of B 10 dB =16 GHz respectively with a fractional -10dB-bandwidth of 20 %. An axial ratio below AR<; 5 dB is achieved within the entire B-10 dB and even AR<; 3 dB within B-15 dB in main lobe direction. The realized antenna gain ranges at G LP ≈11 dBi in linear polarization component yielding a circular polarization gain of G CP ≈12 to 13 dBi. Hence, measurements suggest general feasibility of the proposed helix antenna for mmWave applications despite the relatively high structure complexity due to the miniaturized dimensions at the aimed frequencie